The text: Matlala, Schiodimela, Mamogobo - Groenewald, P. S. (South African Journal of African Languages, 1992)
During the forties Matlala's tšhukudu, Sehlodimela's Moelelwa and Mamogobo's Kxamphuphu were published. Hereafter these books were revised and greatly changed. This fact brings the student of Northern Sotho literature to the point where the concept of the text calls for a final definition. The text is a manifestation of the work of literature. It is connected with the moment of contact between the 'producer' and the 'receiver', and exists for that matter, in time; is bound to a place and an occasion. The different editions of the above-mentioned books are called alternative texts.